Comprehension, Pupil Book 4 - Jackman, John (London, Collins Educational., 2011)
Collins Primary Focus: Comprehension Pupil Book 4 is aimed at ages 10+. Using a variety of well-known authors, the book is designed to encourage children to read and understand every essential fiction and non-fiction text type. Follow-up activities progress from literal questions to higher order thinking skills.